SOCIALIZATION OF CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) EFFORTS TO INCREASE LEARNING ENTHUSIASM IN ELEMENTARY SCHOOL STUDENTS - Tampubolon, Sutar Oktaviana; Sihombing , Vera Ironita Christiani; Sirait , Syarif Hussein; Purba, Yunika Eka Prasetia br; Damanik, Kristin Suriani br (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Clean and healthy community that must be practiced continuously so that it becomes a habitual pattern. Living a clean and healthy lifestyle must be done wherever we are. Moreover, nowadays, children living behavior (PHBS) is an action or activity carried out by a person or are lazy about maintaining cleanliness, for example washing their hands before eating, brushing their teeth before sleeping and so on. Children have more potential to imitate adult behavior, rather than carrying out commands (voices) or instructions from adults. Adults must practice clean and healthy living behavior continuously (consistent) and correctly, both at home and outside the home. That way, children will have a pattern of clean and healthy living behavior that will be practiced throughout their lives. The problem with students at SDN 106168 is that there are still students who snack randomly, throw rubbish out of place, during breaks students play under the hot sun so they sweat and smell like sweat, and they don't wash their hands after playing or doing activities outside the classroom. Thus, we as proponents want to provide socialization activities on the benefits and disadvantages of clean and healthy living behavior efforts. It is hoped that this activity can provide benefits for students in increasing their enthusiasm for learning.